Skarby baroku między Bratysławą a Krakowem = Treasures of the baroque : between Bratislava and Krakow - Chmelinová, Katarína; Betlej, Andrzej 1971-; Kusá, Alexandra (Muzeum Narodowe w Krakowie, 2017)
It is the first big exclusive exhibition of Baroque art from Slovakia in Poland. The exhibition exploits the unique opportunity to present the Baroque art from the collection of Slovak National Gallery in wider spectrum due to the refurbishment of its premises. The exhibition will consist of High and Late Baroque paintings and sculptures from the Slovak National Gallery in Bratislava accompanied by artworks from 17 other Slovak establishments, as well as the 'complementary artworks' from Poland, Ukraine, Hungary and Czech Republic. In the centre-point of the exhibition project (with around 160 items) is the introduction to the Baroque art in Slovakia. 00Exhibition: National Museum in Krakow, Poland (10.02.-23.04.2017)
Bibliogr. s. 303-312. Indeksy
Keywords: Barock; Kunst; Polen; Ausstellungskatalog -- Muzeum Narodowe w Krakowie -- 10.02.2017-23.04.2017 -- Krakau; Bildband